Pengaruh model pembelajaran situation-based learning terhadap kemandirian belajar dan kemampuan pemecahan masalah matematika di SMP - Putri, Maya Angeliana; Mirza, Ade; Hartoyo, Agung; Jamiah, Yulis; Munaldus, Munaldus (Journal of Didactic Mathematics, 2024)
The purpose of this study was to see whether the situation-based learning model can increase students' learning independence and ability to solve mathematical problems in class VIIA SMP Negeri 8 Pontianak. This study used an experimental method with a sample of 31 students. The instruments used in this study were questionnaires and tests. The data analysis technique used was hypothetical statistical test, t test, and product moment test. Based on the analysis, it is concluded that: 1) students' learning independence is in the high category (94%), 2) in the t-test the results obtained t_hitung â‰¥ t_tabel or 1.871 â‰¥ 1.697 in accordance with the testing criteria, the situation-based learning model affects the ability to solve math problems, 3) there is no significant relationship between learning independence and the ability to solve math problems. Therefore, the application of the situation-based learning model has a positive influence on learning independence and the ability to solve math problems of students in class VII SMP Negeri 8 Pontianak.